Fast single metal cation conduction in ion-water aggregated aqueous battery electrolytes - Chen Xu; Huijian Wang; Chengjun Lei; Jinye Li; Wenjiao Ma; Xiao Liang (Nature Communications)
Abstract Metal ion transport in solution is closely linked to its interactions with counter anions and solvent molecules. This interplay creates a longstanding trade-off between transference number (tM n ⁺), ionic conductivity (δ), and solvation process. Advanced aqueous batteries with metal negative electrode require electrolytes with unity tM n ⁺, high δ and low solvation energy. Here we introduce guanidinium sulfate (Gdm2SO4) into metal sulfate aqueous solutions to construct the ion-water aggregated electrolytes. These electrolytes exhibit fast single ion conduction, approaching unity tM n ⁺ and high δ over 50 mS cm−1 for various metal cations (M= Zn, Cu, Fe, Sn and Li). The ion-water aggregates, dynamically formed by strong hydrogen bonding between sulfate anions, guanidinium cations and water, featuring an unfrustrated topological structure to suppress both anion mobility and water activity. This general configuration decouples the metal charge carrier from its coordination sheath, resulting in decreased solvation energy. These merits lead to homogeneous metal plating/stripping behavior with high coulombic efficiency of 99.9%. Moreover, the ion-water aggregates with reinforced kosmotropic characteristics significantly decrease the freezing point of the sulfate-based electrolytes to –28 oC, making them widely applicable in aqueous metal batteries for both intercalation and conversion positive electrodes.